2009
DOI: 10.1093/occmed/kqp072
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and work-related stressors among UK veterinary surgeons

Abstract: Compared to the general population, the sample reported higher risk of work-related stress for demands and managerial support but lower risk for relationships and change. The results could be used to inform the development of targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 21 publications
9
128
3
2
Order By: Relevance
“…In this paper, particular consideration is given to the concept of ‘countervailing interventions’ – those focused on increasing the positive experience of work rather than decreasing the negative aspects – by incorporating some of the sources of satisfaction in veterinary work identified by Bartram and others (2009c), as these may help counteract the effects of workplace stressors (Kelloway and others 2008). Proposed interventions are summarised in Tables 1 and 2.…”
Section: Implications For the Professionmentioning
confidence: 99%
“…In this paper, particular consideration is given to the concept of ‘countervailing interventions’ – those focused on increasing the positive experience of work rather than decreasing the negative aspects – by incorporating some of the sources of satisfaction in veterinary work identified by Bartram and others (2009c), as these may help counteract the effects of workplace stressors (Kelloway and others 2008). Proposed interventions are summarised in Tables 1 and 2.…”
Section: Implications For the Professionmentioning
confidence: 99%
“…* statistically significant (p<0.05) @ C I C E d i z i o n i I n t e r n a z i o n a l i confirmed the factorial structure and showed significant associations with other indicators linked to workrelated stress such as anxiety, depression, job satisfaction and frequency of sick leave (19,20). On the base of the results of these studies, the HSE questionnaire is considered a valid and reliable tool for the assessment of work-related stress.…”
Section: Perceived Stress and Hepatic Parametersmentioning
confidence: 59%
“…), and in the in-depth evaluation of the subjective perception of the workers of the stress related factors. The psychometric properties of this questionnaire were analyzed in many studies (19,20), which confirmed the factorial structure and showed the presence of significant associations with other indicators related to job stress such as anxiety, depression, work, satisfaction with the work and the frequency of sick leave. From the results of this research, the HSE questionnaire is considered one of the most valid and reliable instrument for the assessment of work-related stress.…”
Section: Introductionmentioning
confidence: 68%
“…In contrast to the United States, Bartram, Yadegarfar, and Baldwin (2009) found the top stressors for veterinarian staff in the United Kingdom were the number of hours worked, mistakes, and professional liability. Results from Black et al's (2011) study revealed that Australia's veterinary nurses perceive their jobs as highly demanding and felt confined by a lack of social support and control within their work environment.…”
Section: Sources Of Compassion Fatiguementioning
confidence: 87%